Aplikasi Inderaja dan SIG untuk Monitoring Keberhasilan Reboisasi di Kabupaten Kupang Propinsi Nusa Tenggara Timur - Irmadi Nahib; Jaya Wijaya (Institut Pertanian Bogor (IPB University), 1999)
Sspatial forestry data are inexorably needed to support the reforestation activities. By using multi-temporal data, reforestation activities can be identified and detected. To accomplish the purpose, this research used Landsat TM data acquired in 1990 and 1995. Remotely sensed data and Geographic Information System (GIS) are methods that can be applied together, to monitor as well as analyze data swiftly and accurately. This research used remotely sensed data to collect land cover features in given area. Geographic Information System is used to capture and to analyse reforestation data. The expected outcome is GIS based forest management strategy making.